2016
DOI: 10.1016/j.jpedsurg.2016.02.069
|View full text |Cite
|
Sign up to set email alerts
|

Image-defined risk factors for nephrectomy in patients undergoing neuroblastoma resection

Abstract: Background Although nephrectomy rates are higher in children with neuroblastoma who have image-defined risk factors and/or high-risk disease who undergo resection prior to chemotherapy, no published data outline the key radiographic and clinical characteristics associated with nephrectomy. Methods With IRB approval, imaging studies of children undergoing primary resection of intra-abdominal neuroblastoma between 2000 and 2014 were retrospectively reviewed. Fisher’s exact and Wilcoxon rank-sum tests were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
2
10
0
2
Order By: Relevance
“…In accordance with prior studies, we too observed a higher rate of operative complications, particularly vascular injury, in tumors that harbored IDRF at time of resection [12,13]. A recent study demonstrated an increased risk of nephrectomy in the presence of specific IDRF involving the renal vessels or tumor infiltration into the kidney parenchyma [10]. Our study supports this concept to assess for potential adjacent organ resection in association with infiltrative IDRF, as we too found a correlation between IDRF and adjacent organ resection.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In accordance with prior studies, we too observed a higher rate of operative complications, particularly vascular injury, in tumors that harbored IDRF at time of resection [12,13]. A recent study demonstrated an increased risk of nephrectomy in the presence of specific IDRF involving the renal vessels or tumor infiltration into the kidney parenchyma [10]. Our study supports this concept to assess for potential adjacent organ resection in association with infiltrative IDRF, as we too found a correlation between IDRF and adjacent organ resection.…”
Section: Discussionsupporting
confidence: 89%
“…The efficacy of current neoadjuvant therapy often can render infiltrative and vessel-encasing NBL more readily resectable. Although IDRFs are potentially useful to assess candidacy for upfront resection, to evaluate response to neoadjuvant chemotherapy, to determine an operative approach, and to anticipate intraoperative challenges, the relationship between IDRF and tumor biology, surgical outcomes, and disease prognosis remains incompletely defined especially in North America [610].…”
mentioning
confidence: 99%
“…The presence of adipose tissue between the tumor and vital structures Контакт Contact Отсутствие видимой прослойки между опухолью и смежной структурой. Для артерии -опухоль охватывает не более 50 % окружности сосуда к ее окружности, для описания вены -при уменьшении диаметра сосуда просвет ее остается доступным для визуализации [29,30]. В исследовании S. Fumino (2015) ретроспективно было установлено, что внесение дополнения о включении прямого контакта с почечной ножкой как фактора риска снизило количество незапланирован-ных нефрэктомий и в целом благоприятно повлияло на прогноз пациентов с НБ, но при этом привело к увеличению числа больных с выявленными абдоминальными факторами риска с 39,5 до 81,6 % [31].…”
Section: наличие жировой ткани между опухолью и жизненно важными струunclassified
“…По данным зарубежных авторов, факторы риска и взаимосвязь опухоли с сосудами наиболее часто являются причинами операционных осложнений. Так, при анализе данных 380 пациентов, из которых 27 провели частичную резекцию почки или нефрэктомию, превалировали именно факторы риска, связанные с прямым контактом или вовлечением в патологический процесс структур почечной ножки [29].…”
Section: The Absence Of a Visible Layer Between The Tumor And The Adjunclassified
“…If one or more of these features have been documented, presurgical chemotherapy should be administered to shrink the tumor and enable safe tumor resection. [ 2 31 32 ] Such as paravertebral locations with spinal canal invasion through intervertebral foramina, laminectomy is indicated only in the presence of rapidly progressive neurological symptoms, as chemotherapy can rapidly reduce the volume of the tumor and relieve compression. [ 33 ] Complete resection can be difficult to attain in this disease because of primary tumor encasement of nerves and blood vessels and frequent regional lymph node involvement.…”
Section: S Urgerymentioning
confidence: 99%